2020
DOI: 10.1016/j.ijrobp.2020.07.1758
|View full text |Cite
|
Sign up to set email alerts
|

Combination Radiation Therapy and PARP Inhibition Enhances Responsiveness To Anti-PD-1 Therapy In Colorectal Tumor Models

Abstract: Materials/Methods: The CSF-1R inhibitor BLZ-945 was used to examine the impact of CSF-1R inhibition on M2 polarization using in vitro assays. Then, using an orthotopic, immunocompetent murine GBM-model, mice were treated with vehicle control, RT, BLZ-945, or RT concurrently with BLZ-945. Survival and changes in the immune landscape were compared between treatment arms. Results: BLZ-945 significantly reduced M2 polarization from bone marrow-derived monocytes in vitro. BLZ-945 alone did not result in improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Radiotherapy was reported to upregulate PD-L1 expression by increasing type I interferon (IFN) in the TME to avoid effector T cells [40,41]. In addition, radiotherapy combined with a programmed cell death protein 1 inhibitor achieved surprisingly encouraging results in colorectal cancer [42], lung cancer [43], Merkel cell carcinoma [44], and other cancers. Nevertheless, some side effects (such as noninfectious inflammation) were also observed [45].…”
Section: Radiotherapy Plus Checkpoint Inhibitors a Clinical Study Obs...mentioning
confidence: 99%
“…Radiotherapy was reported to upregulate PD-L1 expression by increasing type I interferon (IFN) in the TME to avoid effector T cells [40,41]. In addition, radiotherapy combined with a programmed cell death protein 1 inhibitor achieved surprisingly encouraging results in colorectal cancer [42], lung cancer [43], Merkel cell carcinoma [44], and other cancers. Nevertheless, some side effects (such as noninfectious inflammation) were also observed [45].…”
Section: Radiotherapy Plus Checkpoint Inhibitors a Clinical Study Obs...mentioning
confidence: 99%
“…It was reported that DDR induced the expression of MHC I and antigen presenting, 74 and PARP inhibition could upregulate MHC I. 75 The PARPi lead to DDR and immunogenic cell death (ICD), thus inducing damage-associated molecular patterns (DAMPs) to promote recruiting APCs. 76 Immune checkpoint inhibitors function to inhibit tumor growth by restoring and enhancing T-cell activation, and T-cell-DC crosstalk involving the cytokines IFN-γ and IL-12 is essential for improved ICI response.…”
Section: Enhanced Antigen Presentationmentioning
confidence: 99%
“…Other strategies have been investigated in preclinical models to increase responsiveness to ICI through induction of proimmunogenic changes in tumor cells. For example, the combination of PARP inhibition (with veliparib) and subablative doses of ionizing radiation was shown in an in vivo unilateral flank tumor model to synergistically increase surface localization of MHC‐1 and PD‐L1 and to prolong anti‐PD1‐mediated tumor growth delay, an effect dependent onCD8 + T‐cells 102 …”
Section: Future Directions and Ongoing Trialsmentioning
confidence: 99%